Automatic driver fatigue detection based on visual computing - Li, Wei (Nanyang Technological University, 2024)
In the context of the growing e-commerce sector, the complexity of supply chains has surged, placing heightened demands on drivers facing increased fatigue. This is particularly critical for timely deliveries of perishable goods and time-sensitive services. To address this challenge and enhance transportation efficiency while mitigating road accidents, a driver fatigue detection system is essential.